2022
DOI: 10.1186/s13293-022-00454-y
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual dimorphism of leptin and adiposity in children between 0 and 10 years: a systematic review and meta-analysis

Abstract: Background Differences in adolescents and adults by sex in blood levels of leptin and adiposity have been described; however, it is not yet clear if these differences arise from the prepubertal stage in subjects with a normal-weight. Therefore, we examine whether there are differences by sex in levels of blood leptin and adiposity in children with a normal-weight between 0 and 10 years old. Methods Search strategy: eligible studies were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 112 publications
0
5
0
1
Order By: Relevance
“…Sex hormones play critical roles in regulating energy metabolism by modulating substrate metabolism, the permeability of retina-and brain-blood barrier, transcriptional factor bindings and epigenetic regulation 34,40,[51][52][53] . The different signaling of sex hormones in the retina, RPE, lens and brain regions 52, 54, from sex chromosomes, sex-different sensitivity to insulin and different levels of adipokines can also contribute to tissue-specific metabolism in different metabolic states [56][57][58][59] .…”
Section: Tissue-specific Sex-different Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex hormones play critical roles in regulating energy metabolism by modulating substrate metabolism, the permeability of retina-and brain-blood barrier, transcriptional factor bindings and epigenetic regulation 34,40,[51][52][53] . The different signaling of sex hormones in the retina, RPE, lens and brain regions 52, 54, from sex chromosomes, sex-different sensitivity to insulin and different levels of adipokines can also contribute to tissue-specific metabolism in different metabolic states [56][57][58][59] .…”
Section: Tissue-specific Sex-different Metabolitesmentioning
confidence: 99%
“…The different signaling of sex hormones in the retina, RPE, lens and brain regions 52, 54, 55 may lead to differential gene expressions and nutrient availability. The differential expression of genes from sex chromosomes, sex-different sensitivity to insulin and different levels of adipokines can also contribute to tissue-specific metabolism in different metabolic states [56][57][58][59] .…”
Section: Tissue-specific Sex-different Metabolitesmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in the affiliations.…”
Section: Correction: Biology Of Sex Differences (2022) 13:47 ...mentioning
confidence: 99%
“…The author group above has been corrected to reflect the updated affiliations. The original article [ 1 ] has been corrected.…”
Section: Correction: Biology Of Sex Differences (2022) 13:47 ...mentioning
confidence: 99%
See 1 more Smart Citation